2018
DOI: 10.3847/1538-4357/aad6e9
|View full text |Cite
|
Sign up to set email alerts
|

VEGAS: A VST Early-type Galaxy Survey. III. Mapping the Galaxy Structure, Interactions, and Intragroup Light in the NGC 5018 Group

Abstract: Most of the galaxies in the Universe at present day are in groups, which are key to understanding the galaxy evolution. In this work we present a new deep mosaic of 1.2 × 1.0 square degrees of the group of galaxies centered on NGC 5018, acquired at the ESO VLT Survey Telescope. We use u, g, r images to analyse the structure of the group members and to estimate the intra-group light. Taking advantage of the deep and multiband photometry and of the large field of view of the VST telescope, we studied the structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(121 citation statements)
references
References 80 publications
(143 reference statements)
13
108
0
Order By: Relevance
“…However, the accurate PSF deconvolution they applied indicates that the broadening takes effect at surface brightness levels fainter than μ r = 25 mag arcsec −2 (see their Figure 12). Results similar to Trujillo & Fliri () for the Gran Telescopio de Canarias+OSIRIS camera have been obtained by Spavone et al () and Cattapan et al () using VST + OmegaCam at ESO. We need to consider two facts.…”
Section: Observations and Reductionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the accurate PSF deconvolution they applied indicates that the broadening takes effect at surface brightness levels fainter than μ r = 25 mag arcsec −2 (see their Figure 12). Results similar to Trujillo & Fliri () for the Gran Telescopio de Canarias+OSIRIS camera have been obtained by Spavone et al () and Cattapan et al () using VST + OmegaCam at ESO. We need to consider two facts.…”
Section: Observations and Reductionsupporting
confidence: 81%
“…Very deep optical observations (e.g., Cattapan et al ; Spavone et al ; Trujillo & Fliri ) reaches surface brightness levels below 29–30 mag arcsec −2 in the r SDSS band. The detailed study by Trujillo & Fliri () showed that galaxies may be broadened in their outskirts by the PSF wings that scatter light.…”
Section: Observations and Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These relics of violent accretion have been predicted by numerical simulations as the most direct evidence for hierarchical clustering (Bullock & Johnston 2005;Johnston et al 2008;Rudick et al 2009;Cooper et al 2010;Puchwein et al 2010;Cooper et al 2013;Rodriguez-Gomez et al 2016;Harris et al 2017). They have been discovered around local late-type galaxies (e.g., Martínez-Delgado et al 2010;Chonis et al 2011;Ibata et al 2014;Foster et al 2014;Amorisco et al 2015;Merritt et al 2016) and local early-type galaxies (Tal et al 2009;Duc et al 2015;Bílek et al 2016;Crnojević et al 2016) as well as galaxy groups (Da Rocha et al 2006;Watkins et al 2014Watkins et al , 2015Okamoto et al 2015;Spavone et al 2018) and galaxy clusters (Feldmeier et al 2002;Arnaboldi et al 2012;Mihos et al 2017;Iodice et al 2016Iodice et al , 2017Iodice et al , 2018. A review on the topic can be found in Carlin et al (2016).…”
Section: Accretion and Merging Signaturesmentioning
confidence: 91%
“…These unbound stars then virialize in the cluster and add up to the ICL budget. For instance, unprecedentedly deep photometric surveys of the Virgo (Mihos et al 2017) and Fornax clusters (Iodice et al 2016(Iodice et al , 2017(Iodice et al , 2018 have unveiled multitudes of tidal streams. Other examples have been discovered in the Coma and Centaurus Clusters (Gregg & West 1998;Trentham & Mobasher 1998;Calcáneo-Roldán et al 2000).…”
Section: Accretion and Merging Signaturesmentioning
confidence: 99%